Development of Engklek Kedamaian Game with Group Guidance to Reduce Aggressive Behavior in Students - Elya Rukhana; Wahyu Nanda Eka Saputra; Nur Azizah; Panji Nur Fitri Yanto; Rita Ika Izzaty (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Learning at school serves to foster and develop compassion and mutual respect for one another. The problem of aggressive behavior in the school environment is still experienced by students. This research is a development research with the aim of knowing the feasibility of media products in the form of engklek kedamaian in group guidance to reduce the aggressive behavior of students in class VIII SMP Muhamadiyah 3 Depok. Researchers used the Brog and Gall model development method with 5 stages, namely potential problems, data collection, product design, product validation, and design revision. The research instruments used in this study were aggressive behavior scales and interview guidelines. The subjects in the study were 123 students in class VIII of SMP Muhammadiyah 3 Depok. The results in the development are measured based on the assessment of the material expert test getting a score of 91.4 with a very good category. The media expert test scored 87.5 with a very good category, the service expert test/practical expert test scored 93.75 with a very good category. Based on some of these statements, it can be concluded that the engklek kedamaian game in group guidance to reduce the aggressive behavior of class VIII students at Muhamadiyah 3 Depok Junior High School is categorized as suitable for use. It is hoped that the research on the development of engklek kedamaian to reduce students' aggressive behavior can be an alternative service innovation for school counselors.